Pelatihan Penelusuran Sumber Sejarah Lokal Berbasis Website Delpher.Nl Pada Materi Sejarah Kolonial Di SMA - M. Afrillyan Dwi Syahputra; Isjoni Isjoni; Asyrul Fikri; Bunari Bunari; Yanuar Al Fiqri (Arfah BHMS Foundation, 2026)
This community service activity was organized for History Subject Teacher Forum (MGMP) educators in Pekanbaru City, aiming to implement the search for local historical sources via the delpher.nl website. linking these sources to colonial history curricula at the high school level. The program comprised four stages: preparation, search strategy design, training implementation, and evaluation. Throughout the activity, teachers gained the insights and skills needed to explore local historical sources on delpher.nl, analyze the information, and integrate it into classroom instruction on colonial history. The results demonstrate that the training successfully enhanced the teachers' ability to use delpher.nl efficiently, fostered innovation in the development of teaching materials, and supported a history learning process that is engaging, interactive, and grounded in historical values ​​consistent with original records.